2010
DOI: 10.5539/ibr.v4n1p100
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Government Procurement Adoption Behavior amongst Malaysian SMEs

Abstract: The aim of this study is to investigate the relationship between a model of electronic procurement (e-procurement) adoption behavior and the level of Government e-procurement adoption amongst Small Medium Enterprise (SME) in Malaysia. Data was collected through questionnaires that were distributed to SME selected randomly in all SME in Malaysia. The data were analyzed using factor analysis, reliability analysis, independent-sample t-test, descriptive statistics, Pearson Correlation and multiple regressions. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…All the latent variables were positively significant to the intent-to-adopt public e-procurement. our results indicate that a positive and strong relationship (β=0.328) between reduction of monopoly power and intent to adopt public eprocurement which is similar to the research electronic government production behaviour observed amongst Malaysian SMEs conducted by Yusoff & Islam (2011). Monopoly power of officials is one of the critical factors bearing upon opportunities for corruption (Klitgaard, 1988).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…All the latent variables were positively significant to the intent-to-adopt public e-procurement. our results indicate that a positive and strong relationship (β=0.328) between reduction of monopoly power and intent to adopt public eprocurement which is similar to the research electronic government production behaviour observed amongst Malaysian SMEs conducted by Yusoff & Islam (2011). Monopoly power of officials is one of the critical factors bearing upon opportunities for corruption (Klitgaard, 1988).…”
Section: Discussionsupporting
confidence: 68%
“…Similar kinds of research models were presented by Neupane et al (2012a, p 6) as part of an evaluation of the anticorruption capabilities of public e-procurement in developing country. Yusoff & Islam's (2011) study into electronic government procurement adoption behaviour amongst Malaysian SMEs supported this finding. Van der Heijden,Verhagen and Creemers (2003, p 44) presented a research model that furthers our understanding of online purchase intentions: contributions from technology and trust perspective.…”
Section: H2: Higher Level Of Perception Of the Potential Of Public E-supporting
confidence: 67%
“…A similar research model was presented by Chan & Lee (2003) SME e-procurement adoption in Hong Kong and the main aim of Chan & Lee's research was to investigate the determinants of electronic procurement adoption by SMEs. Similarly, another similar research model was presented by Yusoff & Islam's (2011) study into electronic government procurement adoption behaviour amongst Malaysian SMEs. Further, Gefen, Karahanna & Straub (2003) demonstrated a research model on the study of Trust and TAM as it related to online shopping.…”
Section: H3mentioning
confidence: 99%
“…The main objective for adoption of EP are to enhance customer service and satisfaction, to produce highly reliable products, best product performance, to improve product quality, improve on time delivery, Government of India also promotes the adoption of EP for better transparency and to eliminate unethical practices, the extent of use of IT by organization's key suppliers, competitors and customers is significant and security concerns through digital networks seem to be a greater threat [3]. Many developed country such as United States, Canada and Japan are implementing eprocurement [11]. E-procurement refers to the use of integrated information technology systems for procurements function, including sourcing, negotiation, ordering, receipt and post-purchased review [1].…”
Section: A Literature Reviewmentioning
confidence: 97%